The Radial Stapler Facilitates Lung-Conserving Wedge Resections. Issue 5 (September 2020) - Makey, Ian A.; El-Sayed Ahmed, Magdy M.; Jacob, Samuel
Objective: To test whether use of the radial stapler facilitates lung-conserving wedge resections compared to the linear stapler. Methods: A video-assisted thoracoscopic simulation lab was established to compare wedge resections performed only with linear staplers to wedge resections performed with the option of a radial stapler. Preserved sheep lungs were used. The target was a 0.5 cm mark on an ovoid surface of the lung equidistant from all edges. Seven fully trained cardiothoracic surgeons participated. They were instructed to obtain at least a 1 cm margin in all directions from the mark. The surgeons were allowed to work from only 2 preassigned ports. Each resected specimen was weighed. The resection margin was the shortest distance measured from the edge of the mark to the staple line. The mass-to-margin ratio was defined as the mass of the specimen divided by the length of the margin. The results were analyzed using a t -test for 2 independent means. Results: The 17 radial resections demonstrated a significantly better mass-to-margin ratio (3.31 [SD = 1.19]) compared to the 11 linear resections (4.75 [SD = 1.32], t [26] = 3, P = 0.006). Conclusions: In a thoracoscopic simulation, the option of a radial stapler allowed for a better mass-to-margin resection of a small target from a broad surface of the lung than a linear stapler-only option.